The Effect of Therapeutic Horseback Riding on Sensory Processing of Children with Autism - Mariam Essa. Al-Shirawi; Rehab Hassan Al-zayer (European Scientific Journal, ESJ, 2018)
Cross-sectional quasi- experimental research design was carried out to examine whether the delivering series of therapeutic horseback riding intervention resulted in an enhancement of sensory characteristics required for effective sensory possessing in children with autism for the experimental group compared to the control group. The participants of this study were 16 children with autism recruited from Al-Wafaa Center for Autism Related Disabilities in Bhrain. It was hypothesized that children with autism provided with Therapeutic Horseback riding in a natural setting (n= 8) would exhibit improvement in sensory processing compared to children who did not get the treatment (n= 8) following an 8- consecutive weeks of therapeutic horseback riding activity. The result of this study indicated that therapeutic horseback riding has a positive impact on sensory profile of children with autism across all sensory dimensions; visual, auditory, smell, tolerance, dehlez, and movement. Further research is needed to allow the use of larger experimental and control samples, and to allow longitudinal studies in order to evaluate the duration of intervention benefits.